MICROTUBULES AND EARLY STAGES OF CELL-PLATE FORMATION IN THE ENDOSPERM OF HAEMANTHUS KATHERINAE BAKER - Hepler, Peter K. (The Rockefeller University Press, 1968)
A fine structure study of the phragmoplast and developing cell plate has been made on glutaraldehyde-osmium tetroxide-fixed, dividing, cultured cells of the liquid endosperm of Haemanthus katherinae Baker. The phragmoplast arises between the telophase nuclei, usually in association with a remnant strand of spindle elements, and consists of an accumulation of microtubules oriented at right angles to the plane of the future cell plate. The microtubules, which are 200–240 A in diameter, occur in small clusters spaced at approximately 0.2–0.3 µ intervals along the plate. Short interconnections interpreted as "cross-bridges" have been observed between individual microtubules. Within each cluster there is an electron-opaque zone about 0.3 µ in width which can be attributed in part to an overlap of microtubules from both sides of the plate and in part to a local accumulation of an amorphous electron-opaque material. During development these dense zones become aligned in a plane which itself defines the plane of the plate. Vesicles, commonly observed in long files, are derived from a cytoplasmic matrix rich in elements of the endoplasmic reticulum and sparse in dictyosomes. They aggregate between the clusters of microtubules and eventually coalesce to form the cell plate.